Shuttle mission in the mitochondrial intermembrane space. (30th January 2018) - Endo, Toshiya; Tamura, Yasushi
Abstract : Lipid trafficking is essential for biogenesis and maintenance of eukaryotic organelles. In this issue of The EMBO Journal, Saita et al (2018 ) revealed that proteolytic processing by the rhomboid protease PARL in the mitochondrial inner membrane facilitates partitioning of START domain‐containing protein STARD7 to the cytosol and mitochondrial intermembrane space. STARD7 in the mitochondrial intermembrane space functions as a lipid transfer protein to shuttle phosphatidylcholine from the outer membrane to the inner membrane. Abstract : Proteolytic processing allows for STARD7 localization not only in the cytosol but also in the mitochondrial intermembrane space, where STARD7 enables mitochondrial function by shuttling phosphatidylcholine from the outer to the inner mitochondrial membrane.